The role of GOT1 in cancer metabolism - Peng, Huan; Dou, Huihong; He, Sheng; Xie, Yu-an; Zhang, Qinle; Zheng, Jianqiu (Frontiers in Oncology, 2024)
GOT1, a cytoplasmic glutamic oxaloacetic transaminase, plays a critical role in various metabolic pathways essential for cellular homeostasis and dysregulated metabolism. Recent studies have highlighted the significant plasticity and roles of GOT1 in metabolic reprogramming through participating in both classical and non-classical glutamine metabolism, glycolytic metabolism, and other metabolic pathways. This review summarizes emerging insights on the metabolic roles of GOT1 in cancer cells and emphasizes the response of cancer cells to altered metabolism when the expression of GOT1 is altered. We review how cancer cells repurpose cell intrinsic metabolism and their flexibility when GOT1 is inhibited and delineate the molecular mechanisms of GOT1’s interaction with specific oncogenes and regulators at multiple levels, including transcriptional and epigenetic regulation, which govern cellular growth and metabolism. These insights may provide new directions for cancer metabolism research and novel targets for cancer treatment.